"Io credo…": "Professing" faith in Paradiso 24. (August 2021) - Barański, Zygmunt G
Dantists have largely interpreted Paradiso 24 as a dryly intellectual canto that positively engages with medieval scholastic culture. Consequently the poet's treatment of faith is seen as both ideologically unproblematic and as an essentially private declaration. The present article argues that such claims are questionable. In actual fact, Paradiso 24 is highly critical of the academic world, while its treatment of faith, although orthodox, is personal, idiosyncratic, and controversial. In addition, the manner in which Dante presents faith has significant political and social implications especially in the wake of the Fourth Lateran Council of 1215. Finally, the canto in general and its assessment of faith in particular serve to legitimate Dante's status as a scriba Dei, an imperative that destabilizes the coherence of the diegesis.